PROBLEMATIKA PEMBELAJARAN SAINS DITINJAU DARI ASPEK GURU - Sari, Milya (Institut Agama Islam Negeri Imam Bonjol Padang, 2013)
Science Education in Indonesia is still poor. There are many components involved in science education such as the teacher. The myriad flaws of the teacherâs factor must be addressed: the intake of low teacher, teachersâ commitment, performance, the level of teacher education, etc. These are caused by low performance of the principal and the Superintendent and the policies of the Government.Â To overcome these problems, then, it is necessary to improve the following program including training and tutorial programs, etc.Â It is expected that through the efforts of increasing teacherâs quality will improve studentsâ science literacy.